2011
DOI: 10.1590/s1807-59322011000100015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors for anorgasmia among reproductive aged women in Hesarak, Iran

Abstract: INTRODUCTION:Orgasmic dysfunction in women is characterized by persistent or recurrent delay in or absence of orgasm following a normal sexual excitement phase. Research has shown that almost two thirds of women have concerns about their sexual relationship. Sexual dysfunction has many problems for couples; some researchers found that up to 67% of divorces related to sexual disorders.OBJECTIVE:The aim of this cross‐sectional study was to assess the prevalence and related factors of anorgasmia among reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
1
26
0
7
Order By: Relevance
“…Some studies have confirmed this statement, 30 whereas others reveal the opposite: orgasm problems are more common in older women. 31,32 Our research found no association between age and orgasm problems, such as the findings of Fugl-Meyer et al, 2 Laumann et al, 33 and Oberg et al 29 It is possible that older women and younger women have different advantages with respect to achieving orgasm. Although older women may have more sexual experience and greater knowledge of their own body, younger women have more sexual desire, 34,35 which, according to our study, is an important factor for achieving orgasm.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies have confirmed this statement, 30 whereas others reveal the opposite: orgasm problems are more common in older women. 31,32 Our research found no association between age and orgasm problems, such as the findings of Fugl-Meyer et al, 2 Laumann et al, 33 and Oberg et al 29 It is possible that older women and younger women have different advantages with respect to achieving orgasm. Although older women may have more sexual experience and greater knowledge of their own body, younger women have more sexual desire, 34,35 which, according to our study, is an important factor for achieving orgasm.…”
Section: Discussionmentioning
confidence: 52%
“…Such gender inequality issues are apparently associated with lack of formal sexual education and ignorance about sexual anatomy and physiology with presence of conservative beliefs. 26 Therefore, female sexuality and sexual education may be trivialized as a result of sociocultural and/or religious concerns. 26,27 Attainment in formal education (in school) may be expected to decrease FSD.…”
Section: Discussionmentioning
confidence: 99%
“…26 Therefore, female sexuality and sexual education may be trivialized as a result of sociocultural and/or religious concerns. 26,27 Attainment in formal education (in school) may be expected to decrease FSD. However in our analyses, degree of formal education lost statistical significance in regression models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FSFI has received extensive psychometric evaluation in clinical and nonclinical samples [20][21][22]. The FSFI has been previously used to assess FSD among Iranian women [22][23][24][25]. A recent study evaluating the psychometric properties of the FSFI found the translated version to be a reliable and valid tool to screen Iranian women with unknown sexual health status, with Cronbach alpha's ranging from α = 0.72 to α = 0.90, as well as excellent construct validity [22].…”
Section: Female Sexual Dysfunctionmentioning
confidence: 99%